2015
DOI: 10.1021/cg501620g
|View full text |Cite
|
Sign up to set email alerts
|

Cocrystallization of 2,3-Dihydroxynaphthalene with Its para-, meta-, and ortho-Ditoluates: Insight into Cocrystal Formation and Clues for the Construction of Supramolecular Assemblies Capable of Intermolecular Acyl Group Transfer Reactivity

Abstract: 2,3-Dihydroxynaphthalene forms 2:1 cocrystals with its p-ditoluate and 1:1 cocrystals with its m-ditoluate but not with the o-ditoluate. In 2:1 cocrystals of the p-ditoluate, naphthalene diol molecules form a dimeric motif through O−H•••O hydrogen bonding interactions. The adjacent dimers sandwich the molecules of pditoluate through C−H•••π interactions. In 1:1 cocrystals of the mditoluate, naphthalene diol molecules generate a zigzag pattern through O−H•••O hydrogen bonding interaction involving −OH of the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Development of multicomponent crystals or cocrystals of active pharmaceutical ingredients (API) evolved into a contemporary area of research first due to their involvement in enhancing physicochemical properties such as solubility, dissolution rate, bioavailability, stability, hygroscopicity, and compressibility, etc., without altering their therapeutic effect rather than what is offered by conventional free API and second due to academic interests in the molecular recognition driven assembly process. , Constant and consistent effort to develop API cocrystals with suitable cocrystal former offers a much wider range of solid forms by which the physicochemical properties of a drug can be optimized or tailored that could be economically advantageous and intellectually inspiring. Reports on pharmaceutical cocrystals exhibiting polymorphism, an ability of a cocrystal to exist in two or more crystalline forms comprising the same stoichiometry of the components, with different arrangements and/or conformations of the molecules in the crystal lattice are very less in numbers as compared to the polymorphs of the single-component system. Lammerer et al have shown that the compounds that are more prone to exhibit polymorphism can reveal polymorphism in cocrystals too as well as they are more likely to form cocrystals . Recent highlight by Aitipamula et al revealed that 114 cocrystals exhibit either packing or conformational polymorphism out of which only 17 were formed concomitantly.…”
Section: Introductionmentioning
confidence: 99%
“…Development of multicomponent crystals or cocrystals of active pharmaceutical ingredients (API) evolved into a contemporary area of research first due to their involvement in enhancing physicochemical properties such as solubility, dissolution rate, bioavailability, stability, hygroscopicity, and compressibility, etc., without altering their therapeutic effect rather than what is offered by conventional free API and second due to academic interests in the molecular recognition driven assembly process. , Constant and consistent effort to develop API cocrystals with suitable cocrystal former offers a much wider range of solid forms by which the physicochemical properties of a drug can be optimized or tailored that could be economically advantageous and intellectually inspiring. Reports on pharmaceutical cocrystals exhibiting polymorphism, an ability of a cocrystal to exist in two or more crystalline forms comprising the same stoichiometry of the components, with different arrangements and/or conformations of the molecules in the crystal lattice are very less in numbers as compared to the polymorphs of the single-component system. Lammerer et al have shown that the compounds that are more prone to exhibit polymorphism can reveal polymorphism in cocrystals too as well as they are more likely to form cocrystals . Recent highlight by Aitipamula et al revealed that 114 cocrystals exhibit either packing or conformational polymorphism out of which only 17 were formed concomitantly.…”
Section: Introductionmentioning
confidence: 99%
“…Activation of the “methyl group” bit may indicate not only the presence of a methyl group itself but also a longer aliphatic chain, since methyl group usually appears at the end of it. It makes sense to take the methyl group as a negative factor because the methyl group normally does not participate in the formation of traditional synthons and may impede intermolecular interactions by restricting the free rotation of neighboring groups . A statistical survey was also conducted on the whole data set.…”
Section: Resultsmentioning
confidence: 99%
“…It makes sense to take the methyl group as a negative factor because the methyl group normally does not participate in the formation of traditional synthons and may impede intermolecular interactions by restricting the free rotation of neighboring groups. 55 A statistical survey was also conducted on the whole data set. It was found that 52.76% of positive samples do not contain a methyl group for both components (value of PubChem374 equals 0), whereas that value for negative samples is only 39.02%.…”
Section: Acc Tp Tn Tp Fp Tn Fnmentioning
confidence: 99%
“…The crux of this was to decide which other compounds containing ester groups could be cocrystallized with the diol 1 . Our earlier work on the correlation of the incidence of polymorphism with cocrystal formation in disubstituted benzene derivatives had qualitatively suggested that small organic molecules that exhibit polymorphism could be more prone to form cocrystals and that para ‐disubstituted benzene derivatives had a higher propensity to form polymorphs as compared to ortho ‐disubstituted derivatives [24] . Hence we prepared several p ‐substituted dibenzoates of the diol 1 (Scheme 2) and attempted their cocrystallization with the diol 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Our earlier work on the correlation of the incidence of polymorphism with cocrystal formation in disubstituted benzene derivatives had qualitatively suggested that small organic molecules that exhibit polymorphism could be more prone to form cocrystals and that para-disubstituted benzene derivatives had a higher propensity to form polymorphs as compared to ortho-disubstituted derivatives. [24] Hence we prepared several p-substituted dibenzoates of the diol 1 (Scheme 2) and attempted their cocrystallization with the diol 1. Symmetric iodo-dibenzoate 8 was prepared by one step acylation of the diol 1 by p-iodobenzoyl chloride, while the unsymmetric diesters 4-7 were prepared by the sequential acylation of the diol 1 with two different acid chlorides.…”
Section: Resultsmentioning
confidence: 99%